Improving Mathematics Teachers' Competence Through a Technological Pedagogical Content Knowledge Model Assisted by Microsoft Mathematics - Masdelima Sormin; Yus Mochammad Cholily; Dwi Priyo Utomo; Baiduri Baiduri; Riski Baroroh; Elisa Elisa (Postgraduate, University of Mataram, 2026)
This study aims to improve the professional competence of Mathematics teachers in the Teacher Professional Program (PPG) through the application of the Technological Pedagogical Content Knowledge (TPACK) model assisted by Microsoft Mathematics. This research is a classroom action research (CAR) conducted in two cycles. Each cycle consisted of planning, action, observation, and reflection stages. The subjects of this study were 16 in-service PPG participants who are mathematics teachers, selected using purposive sampling technique. Data were collected through teacher professional competence tests and teacher activity observation sheets. Data analysis was performed quantitatively using descriptive statistics and qualitatively using interactive analysis techniques. The results showed that in Cycle I, the completion rate of the teacher professional competence test only reached 50% (8 out of 16 teachers passed) with a percentage of teacher activity observation of 62.5%, which had not met the success indicator (≥80%). After reflection and improvement in Cycle II, the completion rate of the teacher professional competence test increased to 81.25% (13 out of 16 teachers passed) with the percentage of teacher activity observation reaching 83.62%. The improvement in professional competence from Cycle I to Cycle II was 31.25%, while the improvement in teacher activity was 21.12%. These results indicate that the TPACK model assisted by Microsoft Mathematics is effective in improving teachers' understanding of the material, pedagogical abilities, and the integration of technology in mathematics learning. The Technological Pedagogical Content Knowledge (TPACK) model assisted by Microsoft Mathematics has proven to be effective and successful in improving the professional competence of Mathematics teachers in the Teacher Professional Program (PPG). The application of this model is recommended as an alternative strategy for sustainable professional development for mathematics teachers.